Nanoencapsulation of morin hydrate with BSA for sustained drug release in colorectal carcinoma cells: experimental and computational approach - Singh, Sanju Kumari; Srivastav, Amit Kumar; Chaurasiya, Sunaina; Patel, Sunita; Kumar, Umesh; Kulhari, Hitesh (Frontiers in Drug Delivery, 2025)
Colorectal cancer is among the most redundant cancer of the gastrointestinal tract, with its burden expected to rise 60% by 2030. Morin hydrate (MH) is a bioflavonoid with anticancer attributes. However, the implementation of MH is limited due to its hydrophobic properties, along with poor stability and bioavailability. Protein-based nanoparticle may encapsulate the drug and this complex can enhance the drug efficacy and delivery to colorectal carcinoma cells. To investigate the molecular interactions between BSA and MH, the Lamarckian genetic approach was used. In the current study, we prepared BSA encapsulated MH nanoparticles by desolvation method. The characterization of the nanoparticles was done by XRD, DSC, TGA and FTIR was performed to corroborate the results. MHNPs were spherical with a particle size of 90 nm determined by TEM and a zeta potential of −11 ± 5.90 mV. BSA nanoparticles improve the thermal stability and sustained release profile of Morin Hydrate, enabling its application as a phytochemical-based anticancer nanocarrier. The antioxidant test of MHNPs showed higher radical scavenging ability than MH. Additionally, our release investigations show that drug release occurs from the matrix of the nanoformulation to reach the target site efficiently. An increase in the anticancer potential was shown by an in vitro cytotoxicity assay in comparison to MH. These data suggest that MH was successfully encapsulated and enhanced solubility, resulting in greater bioavailability.